Pengaruh Manfaat dan Kualitas Hubungan Relasional terhadap Hasil Pemasaran Relasional: Sebuah Studi terhadap Layanan Suratkabar - A. J. Ibnu Wibowo (Jurnal Administrasi Bisnis, 2009)
The importance of developing and maintaining enduring relationships with customersof service businesses is generally accepted in the marketing literature. A keychallenge for researchers is to identify and understand how managerially controlledantecedent variables influence important relationship marketing outcomes (e.g., customerloyalty and word-of-mouth communication). Relational benefits, which havea focus on the benefits consumers receive apart from the core service, and relationshipquality, which focuses on the overall nature of the relationship, represent twoapproaches to understanding customer loyalty and word of mouth. This article integratesthese two concepts by positioning customer satisfaction and commitment asrelationship quality dimensions that partially mediate the relationship between threerelational benefits (confidence benefits, social benefits, and special treatment benefits)and the two outcome variables. The results indicate that the concepts of customer satisfactionand commitment serve to significantly contribute to relationship marketingoutcomes in services. On the other hand, the data does not approve that there is apositive effect of relational benefits to loyalty.Keywords: relational benefits, relationship quality, relationship marketing outcomes,satisfaction, commitment, loyalty, word-of-mouth communication